Investigation of antimicrobial activity combined preparations for clinical strains of microorganisms isolated from patients with bacterial vaginit - Aslanian, M; Bobritskaya, L; Solonina, N; Osolodchenko, T; Kuchma, I (Annals of Mechnikov’s Institute, 2020)
The problem of bacterial vaginit in some cases the cause of severe infectious diseases genitalia of the fetus and newborn, which can impair the health of future generations. It is noted that the treatment of antibacterial agents observed numerous negative side effects- reducing the biochemical activity of the intestinal microflora, abuse microbiota, leading to the development of dysbiosis, increasing the number of resistant strains of pathogens, the risk of allergic reaction sand immunological disorders. A study was conducted towards finding effective combinations of drugs from different pharmacological groups means to create a combination of drugs. The aim of the study was to develop and explore and Flamini combination of miramistin combined medicines to treat bacterial vaginit. As a result of studies in patients with bacterial vaginit pathological material was isolated and identified 72 strains of microorganisms (Staphylococcus spp, Streptococcus spp, Enterococcus spp, Escherichia coli, Haemophillu sssp, Candida albican sand various strains of anaerobic microorganisms. For the combined treatment of infectious and in flammatory diseases (mixed infections) in humans the combined drugin tablet form. All clinical strains of microorganisms isolated from patients with bacterial vaginit were tested for sensitivity to the combined preparation in tablet form with Flamini and miramistin. The greatest sensitivity to the drugs found clinical strains of microorganisms: Staphylococcu saureus, Staphylococcus epidermidis, Peptococcus niger (diameter zone growth retardation is 25,5-23,5 mm). composition tablets number 1 (0.05 g Flamini, miramistini 0.02 g), which was selected for further study shows bacteriostatic effect against a wide range of microorganisms and fungi Rod Candida. IPC for Staphylococcus sp was 20-25 pg / mL for Streptococcus sp 35,0-40,0 mg / ml, for intestinal group 35,0-40,0 for fungi 30,0 mg / ml unlike pills number 2 and number 3, where the IPC was higher and amounted to 40,0 -55,0 mg / ml. Summing upthe results of experimental studies capsules combined with the composition Flamini and miramistin becon cluded that the most effective eagainst the different clinical strains of microorganism sand fungi is a combination Flamini 0,05g, miramistin 0,02 (tablets number1), giving opportunity to develop drug combinations for use in bacterial vaginit.